2015
DOI: 10.1097/md.0000000000002318
|View full text |Cite
|
Sign up to set email alerts
|

Hemophagocytic Lymphohistiocytosis in Intensive Care Unit

Abstract: Hemophagocytic lymphohistiocytosis (HLH) is a critical condition that may lead to organ failure and early death. The aim of this retrospective observational study was to describe a cohort of HLH patients admitted to intensive care unit (ICU) and investigate the risk factors of early death.A positive HLH diagnosis was defined by an HScore ≥169. Univariate and multivariate analyses were carried out to investigate hospital and 28-day mortality risk factors. Between January 2002 and July 2014, 71 HLH cases were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
3
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(88 citation statements)
references
References 19 publications
3
77
3
5
Order By: Relevance
“…Previous studies also reported an inferior OS of patients with LAHS. Barba et al (26) demonstrated that lymphoma was one of the factors associated with increased mortality in patients with HPS. Tong et al (19) conducted a study of 28 patients with aggressive T-cell LAHS and indicated that the median survival time of the patients was 40 days.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also reported an inferior OS of patients with LAHS. Barba et al (26) demonstrated that lymphoma was one of the factors associated with increased mortality in patients with HPS. Tong et al (19) conducted a study of 28 patients with aggressive T-cell LAHS and indicated that the median survival time of the patients was 40 days.…”
Section: Discussionmentioning
confidence: 99%
“…Die genaue Inzidenz ist nicht bekannt, wird jedoch höher geschätzt als bisher angenommen [4]. Die Letalität ist trotz spezifischer immunsuppressiver Behandlung weiterhin sehr hoch [5]. Generell wird eine genetisch bedingte, sehr gut untersuchte Form bei Kindern von einer durch Triggererkrankungen ausgelösten Form bei Erwachsenen unterschieden [6].…”
Section: Cne Schwerpunkt | Update Sepsisunclassified
“…Die Hyperinflammation resultiert in rezidivierenden Fieberepisoden, Tachykardie, hohen Triglyzeridspiegeln, disseminierter intravasaler Gerinnung (DIC), Hemmung der Hämatopoiese und Endorganschäden mit Multiorganversagen [19] [20]. Nicht selten kommt es dabei zu neurologischen Defiziten, Lungen-, Nieren-, Leber-und/oder Kreislaufversagen [5]. Die Infiltration in Milz und Leber führt häufig zur Hepatosplenomegalie, im Knochenmark zu lebensbedrohlichen Zytopenien mit folglich schweren Blutungen und/oder Sepsis [21].…”
Section: Pathogenese Und Klinisches Bildunclassified
See 2 more Smart Citations